Mimicking Aspects of Frontotemporal Lobar Degeneration and Lou Gehrig's Disease in Rats via TDP-43 Overexpression - Tatom, Jason B; Wang, David B; Dayton, Robert D; Skalli, Omar; Hutton, Michael L; Dickson, Dennis W; Klein, Ronald L (Molecular therapy, 2009)
Since the discovery of neuropathological lesions made of TDP-43 and ubiquitin proteins in cases of frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS), there is a burst of effort on finding related familial mutations and developing animal models. We used an adeno-associated virus (AAV) vector for human TDP-43 expression targeted to the substantia nigra (SN) of rats. Though TDP-43 was expressed mainly in neuronal nuclei as expected, it was also expressed in the cytoplasm, and dotted along the plasma membrane of neurons. Cytoplasmic staining was both diffuse and granular, indicative of preinclusion lesions, over 4 weeks. Ubiquitin deposited in the cytoplasm, specifically in the TDP-43 group, and staining for microglia was increased dose-dependently by 1–2 logs in the TDP-43 group, while neurons were selectively obliterated. Neuronal death induced by TDP-43 was pyknotic and apoptotic. TDP-43 gene transfer caused loss of dopaminergic neurons in the SN and their axons in the striatum. Behavioral motor dysfunction resulted after TDP-43 gene transfer that was vector dose-dependent and progressive over time. The cytoplasmic expression, ubiquitination, and neurodegeneration mimicked features of the TDP-43 diseases, and the gliosis, apoptosis, and motor impairment may also be relevant to TDP-43 disease forms involving nigrostriatal degeneration.